Plastic and its Side Effects on Humans – A Review Article - Govind, Aswathi; K, Nishitha (Asian Pacific Journal of Environment and Cancer, 2023)
Plastics are non-biodegradable synthetic substances produced by chemical reactions. Except few test resins derived from corn and other organic substances, almost all plastics are made from carbon and petroleum. The invention of plastics alterated our society by introducing a huge spreading of products and has displaced many traditional materials. We use plastic in countless ways in our daily life such as food storage containers, electric wiring, toys, furniture, clothes, injection, syringes water, and milk bottles, packaging and carry bags, pipes, electronic items, frames, and other several thousands of items. A polymer of carbon and hydrogen alone or with nitrogen, chlorine, oxygen, or sulfur is the backbone of the majority of plastics. Plastic is a non- biodegradable material. Plastic pollutes the air, earth, and water as they contain toxic chemicals. Ethylene oxide, benzene, and xylenes are highly toxic and these are the major chemicals that go into the making of plastic and cause a serious threat to living being of all species on earth. These chemicals can cause disorders ranging from birth defects to cancer, damage the nervous system and the immune system and also affect the blood and the kidneys. Also, many toxic gases are emitted during recycling of plastic. More than 100 million tons of plastic are produced worldwide each year. Plastics do not undergo bacterial decomposition and the disposal of plastic through recycling, burning, or landfilling is a fable. Plastic wastes clog the drains and thus hit especially urban sewage systems. The plastic contaminates the water, soil, marine life and also the air we breathe, causing countless problems to living organism.